THE EFFECT OF DELETION POLYMORPHISM IN THE GSTM1 AND GSTT1 GENES ON THE DEVELOPMENT OF OCCUPATIONAL SENSORINEURAL HEARING LOSS - Смирнова, Елена Леонидовна; Потеряева, Елена Леонидовна; Фунтикова, Инна Сергеевна; Максимов, Владимир Николаевич (Medicine in Kuzbass, 2025)
The analysis of the relationship of genetic markers with occupational diseases helps to identify groups with an increased predisposition to certain diseases among workers and develop timely preventive measures. To identify markers affecting the development of occupational sensorineural hearing loss (PNST), molecular genetic testing of genes was performed to assess their role in the formation of sensitivity to industrial noise. The aim of the research – to analyze the effect of deletion polymorphism in the GSTM1 and GSTT1 genes on the timing of the development of PNST in order to develop criteria for the selection of persons requiring observation and rehabilitation. Materials and methods. 237 men were examined. Of these, 152 people with PNST and 86 people are workers of noise-hazardous professions without PNST. Patients with PNST were divided into two groups depending on the timing of the disease development. Group 1 – 58 people with early onset of the disease (work experience in noise for less than 15 years), group 2 – 94 people with late onset of the disease (work experience in noise for more than 15 years). The following genetic markers were analyzed: deletion polymorphism in the GSTM1 and GSTT1 genes. The statistical analysis was performed in the software environment of RStudio software, Inc., Boston, MA, version 1.2.1335. Results. The results of a study of a number of variants of the nucleotide sequence (GNP) selected on the basis of available data on their role and participation in the pathogenesis and formation of predisposition to PNST are presented, as well as an analysis of existing associations. Conclusion. Genetic markers associated with the late development of PNST have been identified: deletion of GSTT1 in the normal GSTM1 gene. The double deletion of GSTT1/GSTM1 is associated with the absence of disease in workers in noise-hazardous professions (low risk of development).